Dinamika Lembaga Pendidikan Islam di Pasaman Barat (Studi Kasus SMP Islam Terpadu Tahun 2008-2022) - Masfalinda, Masfalinda; Chaniago, Danil Mahmud; Riza, Yulfira (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2024)
This research is motivated by the existence of an integrated Islamic education institution in West Pasaman Regency which emerged in 2008. The focus of this research is on the history of the establishment of Integrated Islamic Junior High School and its influence on the lives of the people of West Pasaman. This research was conducted using historical research methods with the steps of heuristics, source criticism, synthesis and historiography. Assisted by the use of social change theory to see the phenomena that occur and as an analysis knife. The results of this study reveal that the presence of Darul Hikmah IT Junior High School since 2008 and Al-Kahfi IT Junior High School in 2017 has given a new color to the world of education in West Pasaman. The existence of integrated Islamic schools has influenced various aspects of community life, including religion, education, politics, economy and culture. In the economic field, IT Junior High School has an impact on increasing the standard of living of the people of West Pasaman for the better. In the field of education itself, it can be seen from the addition of new educational institutions that imitate the learning patterns applied in Integrated Islamic Junior High School. In the political field, visible changes in the development of human resources such as teachers and students at IT Junior High School through leadership training and the formation of an IT Junior High School organizational network within the scope of the Integrated Islamic School Network (JSIT), JSIT is motivated by political parties and political party cadres. In addition, the fulfillment of IT Junior High School facilities and amenities is also assisted by political parties and political activists. With this political role, it then has an impact on improving facilities and infrastructure that affect the development of schools.